The Rabbit as a Model for Studying Lung Disease and Stem Cell Therapy. (4th April 2013) - Kamaruzaman, Nurfatin Asyikhin; Kardia, Egi; Kamaldin, Nurulain 'Atikah; Latahir, Ahmad Zaeri; Yahaya, Badrul Hisham
Abstract : No single animal model can reproduce all of the human features of both acute and chronic lung diseases. However, the rabbit is a reliable model and clinically relevant facsimile of human disease. The similarities between rabbits and humans in terms of airway anatomy and responses to inflammatory mediators highlight the value of this species in the investigation of lung disease pathophysiology and in the development of therapeutic agents. The inflammatory responses shown by the rabbit model, especially in the case of asthma, are comparable with those that occur in humans. The allergic rabbit model has been used extensively in drug screening tests, and this model and humans appear to be sensitive to similar drugs. In addition, recent studies have shown that the rabbit serves as a good platform for cell delivery for the purpose of stem-cell-based therapy.